Outcomes of adult-to-adult living donor liver transplantation： a single center experience - Feng, Xi; Yuan, Ding; Wei, Yong-Gang; Li, Fu-Qiang; Wen, Tian-Fu; Zeng, Yong; Zhao, Ji-Chun; Wang, Wen-Tao; Xu, Ming-Qing; Yang, Jia-Yin; Ma, Yu-Kui; Chen, Zhe-Yu; et al. (Chinese medical journal, 2009)
Background Since January 2002, adult-to-adult living donor liver transplantation （AALDLT） has gained increasing popularity in China in response to the shortage of cadaveric donor livers. This study presents a detailed analysis of the outcomes of AALDLT in a single center. Methods A total of 70 patients underwent AALDLT at our center between January 2002 and January 2007. Among these, 67 patients received a right lobe graft without the middle hepatic vein and 3 patients received dual grafts. Three-dimensional volumetric computed tomography, magnetic resonance imaging with angiography and cholangiography were performed preoperatively. Recipient operation time, intraoperative transfusion requirement, length of intensive care unit stay, length of hospital stay, liver function tests, coagulation tests and surgical outcomes were routinely investigated throughout this study. Results All donors survived the procedure with an overall complication rate of 15.3%. Overall recipient 1-year survival and complication rates were 87.1% and 34.2%, respectively. Among the 70 cases, average graft recipient weight ratio was 0.94% （0.72%-1.43%） and average graft volume/standard liver volume ratio was 46.42% （31.74%-71.68%）. All residual liver volumes exceeded 35%. Liver function and coagulation recovered rapidly within the first 7 days after transplantation. Conclusions AALDLT is a safe procedure for the donors and an effective therapy for patients with end-stage liver disease. Patient selection and timely decision-making for transplantation are essential in achieving good outcomes. With accumulation of experience in surgery and clinical management, timely feedback and proper modification, we foresee better outcomes in the future.